12x+9y=9y

Simple and best practice solution for 12x+9y=9y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x+9y=9y equation:


Simplifying
12x + 9y = 9y

Add '-9y' to each side of the equation.
12x + 9y + -9y = 9y + -9y

Combine like terms: 9y + -9y = 0
12x + 0 = 9y + -9y
12x = 9y + -9y

Combine like terms: 9y + -9y = 0
12x = 0

Solving
12x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '12'.
x = 0

Simplifying
x = 0

See similar equations:

| 3b-8(2b-3)=102 | | 9-c^2= | | 2x^2=756 | | 10x-7=91-4x | | 3x+-1=-32 | | 3(-4-9n)-6n= | | 84=6(2-x)-3x | | -2=-2(n-8) | | 7(-4-5p)-4=-207 | | 5x+4-7x=5+x+13 | | 29+2x=x+25 | | 8-3y=-4 | | 4x^3+x^3+9x^2=0 | | -102=-2(8-7r)-2 | | x-3(8)=-4 | | y=50x+90 | | 2x+27=x+21 | | 4(v+7)=6v+18 | | 31=7+3x | | (2x-5)(2x-5)-121=0 | | 8(1-2r)=-88 | | 18+x=x+23 | | 7-3a=-16 | | -2x+4=5+1x-13 | | 4x+y-47=0 | | 4u+36=6(u+4) | | 3x+1=4+x | | (2x)+x+(2x+5)=50 | | 3p^2-9p-1=0 | | 2b-67=-8n+5 | | -6n=27 | | (c+3)-(1-3c)=2 |

Equations solver categories